Effects of Energy and Dietary Fiber on the Breast Development in Gilt - Xu, Shengyu; Tang, Lianchao; Xu, Haitao; Yang, Yi; Cao, Meng; Chen, Sirun; Jiang, Xuemei; Li, Jian; Lin, Yan; Che, Lianqiang; Fang, Zhengfeng; Feng, Bin; et al. (Frontiers in Veterinary Science, 2022)
To study the effects of energy and dietary fiber on the breast development in gilts and its possible mechanisms, 32 gilts (Landrace × Yorkshire) were randomly allocated into a 2 × 2 factorial design to receive a diet with low or high energy (LE: 33.37 MJ/d DE; HE: 41.87 MJ/d DE), and low or high fiber (LF: 0.3 kg/d dietary fiber, HF: 0.6 kg/d dietary fiber). The weight of breast tissue was recorded. The mammary glands were collected for further analyses. The high energy intake increased the relative weight of breast tissue (p < 0.05) and the content of breast fat (p < 0.05). At the same time, the oil red staining of breast slices also showed an increase in breast fat content in high energy treatment. High energy intake increased the DNA concentration in breast tissues (p < 0.05). In addition, high energy intake increased the concentration of triglycerides, free fatty acids and total cholesterol in the blood of gilts (p < 0.05), and the supplementation of high fiber tended to reduce free fatty acids, total cholesterol and estradiol (p < 0.1). Proteomic analysis suggested that there were notable differences in cytoskeleton, intracellular non-membrane bounded organelle, apoptosis, receptor activity and endopeptidase inhibitor activity in molecular function between the energy and fiber effects (p < 0.05). High fiber intake also decreased the mRNA expression of 5-HT7, Bax and Caspase-3 in breast tissue of gilts (p < 0.05), which further confirmed the importance of fiber in regulating breast development in gilt. Our results indicated that increasing gilts energy intake improved breast weight, fat deposition, and increased breast cell apoptosis. Increased fiber intake reduced breast fat deposition and breast cell apoptosis at high-energy intake in gilts. These results provide a potential strategy for dietary intervention against high-energy intake in gilts and even in human.